Reforming Civil Justice Systems : Trends in Industrial Countries - Zuckerman, Adrian A.S. (World Bank, Washington, DC, 2012)
Civil justice reform efforts in industrial countries face common problems in increasing access to justice and reducing costs and delays. A recent survey examined problems with and reforms of civil justice in 3 common law nations and 10 civil law countries. All reported that the economic interests of the legal profession explain many of the costs and delays in litigation and that overcoming these interests is difficult. Both civil and common law countries are resorting to greater judicial control of litigation process to control lawyers and their clients. There is the appearance of a new theory of civil procedure: the resources devoted to resolving a dispute should be proportionate to the interests involved and that systemwide resources should be allocated fairly across all disputes.